Improving Students’ Understanding in Practicing Static and Dynamic Gymnastic Movements through Audio Visual - Rozaq, Andri Buldani; Wardiah, Dessy; Manullang, Jujur Gunawan (Yayasan Sembilan Pemuda Indonesia, 2023)
The purpose of this study was to determine the effect of using audio-visual media on increasing students' understanding of practicing static and dynamic gymnastics movements. This form of research is using the One Group Pretest-Posttest Design research design. The subjects of this study were VII grade students of SMP Negeri 3 Ulu Musi, namely where the number of students was 20 students, namely 11 boys and 9 girls. The research data analysis technique was carried out by comparing the data from the pretest and posttest results after treatment using a one-sample t-test. From the results of the study before students saw audio-visual media, the average pretest result was a question item value of 48.05 with the highest value of 72, and the lowest value was 14. The average pretest skill value was 56.56 with the highest value of 87.5 and the lowest value was 25. Whereas during the posttest after students saw audio-visual learning media, the average value was a question item value of 95.8 with the highest value of 100 and the lowest value of 75. The average skill value was 85.93 with the highest post-test value of 100 and the lowest value of 62.5. Thus, showing an increase in student understanding in practicing static and dynamic gymnastics movements through audio-visual media from the pretest and post-test. This proves that the use of audio-visual media is effective in increasing students' understanding of practicing static and dynamic gymnastics.